Conservation of cultural heritage buildings: Methodology and application to case studies - Lourenço, P. B. (Revista ALCONPAT, 2013)
Modern societies understand built cultural heritage as a landmark of culture and diversity. Only during the last decades the idea that ancient buildings could be conserved and reused became appealing. Still, a large part of this heritage is affected by structural problems which menace the safety of buildings and people. The developments in the areas of inspection, non-destructive testing, monitoring and structural analysis of historical constructions, together with recent guidelines for reuse and conservation, allow for safer, economical and more adequate remedial measures. The paper addresses the issues of the methodology to adopt, of different cases studies and of present challenges. In particular, recent interventions in Portuguese cases studies (the Cathedral of Porto and a theological school in Braga) are analyzed in detail.